БІОСТРАТИГРАФІЯ КІМЕРИДЖСЬКИХ ВІДКЛАДІВ ПЛАТФОРМНОЇ УКРАЇНИ (ВЕРХНЯ ЮРА) - Piatkova, D. (Institute of Geological Sciences of the Ukrainian National Academy of Sciences, 2012)
The results of the study of the stratigraphy of Kimmeridgian deposits (Upper Jurassic) of the Dnieper-Donets basin and the north-western margin of the Donbas, given their paleontological study.